Aberrant expression of SATB2, CDX2, CDH17 and CK20 in hepatocellular carcinoma: a pathological, clinical and outcome study. Issue 5 (3rd August 2021) - Kmeid, Michel; Lukose, Georgi; Hodge, Kyle; Cho, Daniel; Kim, Kelly‐Ann; Lee, Hwajeong
Abstract : Aims: Data regarding expression of intestinal markers in hepatocellular carcinoma (HCC) are limited. We determined the clinicopathological associations of cytokeratin (CK)19, a progenitor liver epithelial cell marker as well as biliary epithelial marker, and intestinal immunohistochemical markers expression in HCC and assessed their prognostic value. Methods and results: Tissue sections and/or tissue microarrays (TMAs) from 202 known HCCs were immunostained using CK19, CK20, CDH17, CDX2 and SATB2 antibodies. Haematoxylin and eosin (H&E)‐stained slides were reviewed for tumour grading. Clinical and oncological outcomes were retrieved. Associations of staining with clinicopathological features and survival outcomes were evaluated. CK19, CK20, CDH17, CDX2 and SATB2 were positive in 12.8, 5.4, 10.3, 8.6 and 59.9%, respectively. All but SATB2 were strongly associated with higher tumour grade and AFP levels > 400 ng/ml ( P < 0.05). CK19‐positive HCC were more likely to express CDX2 ( P = 0.001), CDH17 ( P < 0.001) and/or CK20 ( P = 0.012). CK20, CDX2 and CDH17 co‐expression was seen in five cases (2.5%). CK19 and SATB2 positivity, tumour size ≥ 5 cm, background cirrhosis, AFP > 400 ng/ml and having no treatment were associated with decreased overall survival by log‐rank test and univariable proportional hazards regression. However, in a multivariable model, CK19 and SATB2 positivity were not independent predictors of decreased survival while their association with known poor prognosticators in HCC was evident. Conclusions: HCC can express markers of intestinal differentiation. This phenotypical aberrancy correlates with variable clinicopathological parameters, some of which are independent predictors of poor survival. Abstract :